Evaluation of the hermeneutic bases of Ayatollah Javadi Amoli and Asma Barlas in the interpretation of "Wadrbohan" - zahra khani; Vahid Sohrabifar (حکمت اسرا, 2024)
Examining the history of interpretation in the context of women shows changes in the field of interpretation of the Qur'an. One aspect of the changes is attention to understanding.Also, the interpretations changed due to socio-cultural changes in the subject. Feminist attitudes are the most important of these developments. Some, like Barlas, have sought answers to feminist demands by using a different reading of the Qur'an. some, like JavadiAmoli, by focusing on the issue of women in the interpretation of the Qur'an, seek to provide new answers, appropriate to contemporary developments; The comparative study of these two attitudes, with the aim of evaluating the impact of the commentators' hermeneutic foundations on their understanding of the verses, shows the necessity of this research. Since the permissibility of beating women in verse 34of Surah Nisa is one of the most challenging issues in the field of women, the hermeneutic foundations of JavadiAmoli and Barlas's point of view in the interpretation of "Wadrbohan" are evaluated with descriptive-adaptive method. According JavadiAmoli's focus on the author and the use of words for the spirit of meanings, the verse may be suitable for the structure of the tribal life system and not the structure of the civil life. As a result, a concept of multiplication can be carried over the present tense.While Barlas, believing in the multiplicity of meanings of the Qur'an does not adhere to some of his hermeneutic bases like the author-centered one, and this leads to the imposition of his opinions on the Qur'an.